(untitled) (Academicia Globe: Inderscience Research, 2021)
The article examines the theoretical and methodological foundations of the processes associated with the conditions and factors of innovative development of the economy of Uzbekistan. The existing opportunities for innovative development of the country’s economy are systematized. Suggestions and recommendations on the possibilities of increasing the efficiency of innovative reforms are given.